Corporate governance, external market discipline and firm productivity - Tian, Gloria Y.; Twite, Garry (Journal of Corporate Finance, 2011)
Using a sample of Australian companies over the 2000–2005 period, we examine the impact of internal corporate governance on firm's total factor productivity, taking into account the interaction between internal governance and external market discipline. Our empirical findings point to a substitution effect between product market competitiveness and firm-level corporate governance. Overall, internal corporate governance mechanisms – more efficient boards and greater CEO stock-based compensation – are effective instruments for improving firm productivity. However, internal governance is less effective when a firm faces a highly competitive product market. We find only weak empirical support for an association between firm's ownership structure and productivity, and no support for an association between industry takeover intensity and firm productivity.